Loanwords and native words in Old and Middle Icelandic (12th c.-1550) - Tarsi, Matteo (HÁSKÓLI ÍSLANDS/UNIVERSITY OF ICELAND, 2020)
This thesis addresses the coexistence and interplay of loanwords and their corresponding endogenous synonyms during the Old and Middle Icelandic period (12th c.–1550), i.e. in a period with no ideologically rooted nor overtly expressed language purism. The purist ideology is first apparent in Iceland in the activities and writings of Bishop Guðbrandur Þorláksson (1542–1627) and of Arngrímur Jónsson the Learned (1568–1648). This study is thus devoted to understanding the dynamics which underlie the retention of inherited lexemes and the creation of new lexical items, whether by the generation of new words (structural calques and neoformations) or by the semantic extension of lexemes through external influence (semantic calques), in contrast with the acquisition of loanwords. The analysis in the present work encompasses all the prosa genres produced during the historical period under scrutiny: religious literature, law texts and charters, treatises, historiography, saga literature (hagiography, family sagas, kings’ sagas, chivalric sagas, legendary sagas). The selection of texts for each genre is balanced with respect to period of production, length and textual transmission. The analysis was carried out according to the following lines of research: 1) With reference to texts and manuscripts a) Intertypological analysis: To investigate whether, and to what extent, different text typologies differ in showing the phenomenon under research. b) Intrastemmatic analysis: To investigate whether different witnesses of a given text differ in the use of loanwords and endogenous words in a specific locus. 2) Typological analysis a) To classify single word pairs according to their semantic field. b) To classify the native words according to their typology (semantic calque, structural calque, neoformation, inherited word), and when possible to identify the foreign source of semantic and structural calques. c) To evaluate single loanwords according to their borrowing typology (necessity vs. prestige loans). 3) Etymology/Word ...